DOI: 10.11606/d.7.2012.tde-08032013-141540
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de qualidade do registro eletrônico do processo de enfermagem

Abstract: Ao meu querido esposo Josenildo, pelo amor incondicional, pelo companheirismo, pela paciência sem limites, pelo apoio irrestrito e fundamental, por toda a ajuda na tabulação dos dados e na elaboração das figuras. Agradeço principalmente pelo cuidado constante com a nossa filha nos momentos em que precisei me ausentar para a elaboração deste trabalho. À minha amada filha Júlia Mariane, que traz alegria e cor para os meus dias e me faz acreditar que nada é impossível para Deus. Sua existência me lembra todos os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
12

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
0
11
0
12
Order By: Relevance
“…(12) According to these recommendations, the PROCEnf-USP® has a standardized system of language, and minimum nursing data that are set to essential data, which are documented in nursing care. (2,5) In the study, 245 diagnoses indicated by the students, 166 (86 [PROCEnf-USP ® ] and 80 [paper-based]) had zero accuracy, that is, 68% of diagnoses. Phenomena like this are foresee in the literature, which in one clinical situation can be identified as highly accurate diagnoses and in another as low accuracy, which is accomplished by the complexity and subjectivity of nursing diagnoses.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…(12) According to these recommendations, the PROCEnf-USP® has a standardized system of language, and minimum nursing data that are set to essential data, which are documented in nursing care. (2,5) In the study, 245 diagnoses indicated by the students, 166 (86 [PROCEnf-USP ® ] and 80 [paper-based]) had zero accuracy, that is, 68% of diagnoses. Phenomena like this are foresee in the literature, which in one clinical situation can be identified as highly accurate diagnoses and in another as low accuracy, which is accomplished by the complexity and subjectivity of nursing diagnoses.…”
Section: Discussionmentioning
confidence: 92%
“…(2,5) In a previous study, the PROCEnf-USP® was assessed for its quality standard requirements ISO/IEC 25010 and the results indicated that the characteristic "Functional Adequacy" reached the quality required for the necessities considered in the assessment of nursing professors, clinical and surgical doctors, among other units, and computer experts. It was evident that, from a functional point of view, the PROCEnf-USP ® is a tool that meets the needs of users, and enable the execution of Nursing Process based on scientific knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations